Primary Splenic Angiosarcoma Presenting as Idiopathic Thrombocytopenic Purpura: A Case Report and Review of the Literature - S. Christopher N. Frontario; Anna Goldenberg-Sandau; Darshan Roy; Roy Sandau (Case Reports in Surgery)
Angiosarcoma of the spleen is a rare malignancy that arises from vascular endothelial origin. This neoplasm is highly malignant and diagnosis is often delayed due to the vague presentation of clinical symptoms. A case report and concise review of the current diagnostic criteria and surgical treatment are provided to aid in the detection and treatment of this malignancy. We present a case of a 56-year-old female who presented with massive splenomegaly secondary to angiosarcoma of the spleen. The patient suffered from longstanding symptomatic anemia and thrombocytopenia. Diagnosis of a splenic angiosarcoma can be difficult due to the vague presentation and lack of concrete risk factors. Early identification and splenectomy are paramount. However, it is an aggressive malignancy with poor prognosis. We reviewed the literature of the current diagnostic and surgical treatment of primary splenic angiosarcoma.